The role of FGF21 and its analogs on liver associated diseases - Falamarzi, Kimia; Malekpour, Mahdi; Tafti, Mobin Fallah; Azarpira, Negar; Behboodi, Mehrdad; Zarei, Mohammad (Frontiers in Medicine, 2022)
Fibroblast growth factor 21 (FGF21) is a hormone-like growth factor that is synthesized mainly in the liver and adipose tissue. FGF21 contributed to many metabolic pathways like decreasing lipogenesis and increasing hepatic insulin sensitivity causing lipid profile improvement. FGF21 variations also affect nutritional and addictive behaviors such as smoking and alcohol consumption and eating sweets. The role of FGF21 in metabolic associated diseases like diabetes mellitus had been confirmed previously. Recently, several studies have demonstrated a correlation between FGF21 and liver diseases. Non-alcoholic fatty liver disease (NAFLD) is the most prevalent type of chronic liver disease worldwide. NAFLD has a wide range from non-alcoholic steatohepatitis (NASH) to fibrosis and cirrhosis. Almost 50% of cirrhosis-related mortality is caused directly or indirectly by alcohol. FGF21 can reverse the progression of alcoholic fatty liver disease(AFLD) and can be used as a biomarker for it. Also, NAFLD and NASH are the most important risk factors for hepatocellular carcinoma (HCC). HCC is the fourth deadliest cancer in the world. In this review article, we intend to discuss different aspects of FGF21 in NAFLD, AFLD and HCC. These aspects are including the pathophysiology of the FGF21 in these diseases, the effects of FGF21 mutations, the use of the FGF21 as a biomarker in different stages of these diseases, as well as the usage of FGF21 and its analog molecules in the treatment of these diseases.